Negev. - Amorai, Shua; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Beer Sheva : Municipality Department of Culture and Special Events, 1994)
Karsenty, Shoshana ; Shelly, Margalit ; Stram, Miriam ; Kroupp, Rachel ; Casapu, Dora ; Manor, Genia ; Meller, Daniella ; Levin-Bar, Sally ; Levy, Yona ; Tushinsky, Dvora ; Vardy, Chana ; Wortman, Danielle ; Derel, Maria & Smelyansky, Elena ; Behar, Laura ; Bowman, Ruth ; Assayag, Moti ; Alkan, Yardena
Negev, Municipal Gallery, City Hall, Beer Sheva, 3.10.94 - 11.11.94
boek
Keywords: Negev